-19g+12-2g=3-4g+8

Simple and best practice solution for -19g+12-2g=3-4g+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19g+12-2g=3-4g+8 equation:


Simplifying
-19g + 12 + -2g = 3 + -4g + 8

Reorder the terms:
12 + -19g + -2g = 3 + -4g + 8

Combine like terms: -19g + -2g = -21g
12 + -21g = 3 + -4g + 8

Reorder the terms:
12 + -21g = 3 + 8 + -4g

Combine like terms: 3 + 8 = 11
12 + -21g = 11 + -4g

Solving
12 + -21g = 11 + -4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '4g' to each side of the equation.
12 + -21g + 4g = 11 + -4g + 4g

Combine like terms: -21g + 4g = -17g
12 + -17g = 11 + -4g + 4g

Combine like terms: -4g + 4g = 0
12 + -17g = 11 + 0
12 + -17g = 11

Add '-12' to each side of the equation.
12 + -12 + -17g = 11 + -12

Combine like terms: 12 + -12 = 0
0 + -17g = 11 + -12
-17g = 11 + -12

Combine like terms: 11 + -12 = -1
-17g = -1

Divide each side by '-17'.
g = 0.05882352941

Simplifying
g = 0.05882352941

See similar equations:

| -16x^2+72x+84=0 | | Y^1/2=1/3 | | 6-(2n-9)=2-3n | | 10x+12y=70 | | 3x+8=9x+32 | | b+46=2b | | -9(5h-3)=30+4h | | 3q^2-10q-77=0 | | 8cos^4x-10cos^2x+2=0 | | -9x+10=-10x+1 | | 136.37=2.45h+72.67 | | 4-7(1+3r)=-24 | | X+(x^2-5)=1 | | 55+f=180 | | -8x+6=4x-90 | | 55=f | | 10b=25 | | HIJK=90 | | x+(x*.10)=64900 | | 14(x-200)=308800 | | 6=8x-2ix | | 24x+8=15-46 | | X-5/9=25/9 | | S/3-4=15 | | 0.5t^2-16=0 | | -4/4x=-8/27 | | 5x+5+4x+5=180 | | e^2x+b=23 | | 6(z-5)=24 | | -2+8u=-50 | | 296+x-24+29=360 | | -2(5s+2)+5(s-3)= |

Equations solver categories